System performance comparison of oxygen consumption and air separation for aircraft fuel tank inerting - Lei Shao; Jingxin Tan; Weihua Liu; Jiahao Yang; Bo Hei; Jiahao Qu (Case Studies in Thermal Engineering, 2024)
To compare the performance of oxygen consumption and air separation inerting systems. This paper established the mathematical models of the oxygen consumption inerting system and air separation inerting system by mass conservation and energy conservation formula, and the equal inerting time method is adopted to assess the overall performance of the two systems. The two system performances, such as volume flow, thermal load, thermal power, mass increment, and additional fuel consumption, are compared. The results show that: The volume flow of the oxygen consumption inerting system is only 22.9% of the air separation system because of its internal circulation air injection characteristics. Furthermore, the thermal load of the oxygen consumption inerting system is reduced by 30% compared to the air separation system. The total additional fuel consumption of the oxygen consumption inerting system is reduced by 93.57% compared to the air separation system.